FEATURES OF APPLICATION OF GAS FUEL IN VEHICLES WITH DIRECT FUEL INJECTION - M. V. Banket (Вестник СибАДИ)
The article reveals the problems of using gas fuel in vehicles with direct fuel injection. Based on the analysis of car sales, the authors found that cars with direct fuel injection are in high demand out of the market of vehicles with a distributed phased fuel injection. The analysis of ways of installation of LPG equipment for vehicles with direct fuel injection. Allocated and describes the characteristics of LPG equipment for vehicles with direct fuel injection. The main contents of the study are the results of bench testing of direct injection engines, working on gas fuel.